Micro‐Supercapacitors: Hydrous RuO2‐Decorated MXene Coordinating with Silver Nanowire Inks Enabling Fully Printed Micro‐Supercapacitors with Extraordinary Volumetric Performance (Adv. Energy Mater. 15/2019). Issue 15 (18th April 2019) - Li, Hongpeng; Li, Xiran; Liang, Jiajie; Chen, Yongsheng
Abstract : In article number1803987 by Jiajie Liang and co‐workers a fully printed strategy is reported to assemble flexible micro‐supercapacitors by printing thixotropic nanocomposite inks for electrodes comprising RuO2 · x H2 O@Ti3 C2 T x (MXene) nanosheets and silver nanowires. The resultant screen‐printed micro‐supercapacitors based on this RuO2 · x H2 O@MXene–AgNW nanocomposite ink exhibit a landmark volumetric capacitance of 864.2 F cm −3 at a scan rate of 1 mV s −1 .